Assessing Response Time Effects of Forward Collision Warning HMIs with Central Tendency, Variance, and Dominance Tests. (September 2014) - Tijerina, Louis; Curry, Reates
Reaction times (RTs) to driver warning system human-machine interface (HMI) designs are often used to assess their impact on driver detection performance. This paper introduces three different ways to statistically compare alternative HMIs in terms of RTs. The most commonly reported way is to compare central tendencies such as RT means or medians. A second approach, less commonly used, compares the variability in RT distributions associated with different HMIs as an assessment of the consistency of response effects elicited by an HMI across participants. The third method is to compare the RT distributions from alternative HMIs by means of ordinal dominance statistics. This assessment directly addresses the question: "Do people tend to respond faster with HMI A than HMI B (or vice versa)?" These alternative assessments are applied to RT data from a simulator study of several alternative forward collision warning (FCW) HMIs and the insights provided by each are discussed.